KESETARAAN GENDER DALAM PENDIDIKAN ISLAM (Studi Pemikiran Pendidikan Hamka dalam Tafsir al-Azhar) - Juono, Ribut Purwo (Analisis: Jurnal Studi Keislaman, 2015)
GENDER   EQUALITY   IN   ISLAMIC   EDUCATION   (Study on Hamka’s Educational  Thought  in His Tafsir al-Azhar):   The research entitled  of equality  of gender in Islamic education  has represent about idea studying that try to express some problems related to equality of gender at scope in Islamic education, specially the  Islamic  education ideas  of  one  of  the modern  Indonesia mufassir,  Hamka.  Target  desired  or like to achieved from  this research is describing Hamka’s education ideas based on equality of the gender perspective. Besides, this research proposed also for understand  the interpretation methodology  used by Hamka and it’s corelation  with his ideas about Islamic education  in gender perspective. This research  explain  also  about  relevance  of his ideas for the developing of national education system. The result of research  is statement that  the theme of gender equality  has not found in Hamka’s education  ideas, but researcher can make conclusion that in general, Hamka’s education ideas has free from misogynist and discriminative opinion to the woman.